2013
DOI: 10.1007/s11255-013-0501-4
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of augmentation cystoplasty in patients suffering from ketamine-related bladder contractures

Abstract: Ketamine cystitis is an emerging medical condition that requires a multi-disciplinary approach to manage the patients. Simple surgical management of the physical component of the contracted bladder may produce only suboptimal results, and could even cause further problems in some patients. The importance of compliance with post-operative care and abstinence from drug use should be stressed to the patients before surgery. In view of the high complication rate, the option of a simple ileal conduit should also be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 18 publications
1
33
0
Order By: Relevance
“…6 Although many recognized that abstinence from ketamine is by far the most effective treatment option, 7 oral or intravesical medication and surgical intervention have been attempted to alleviate the detrimental effect brought along by ketamine abuse on the genitourinary system. 8 We have previously reported a crosssectional study on symptoms and voiding parameters of patients from a dedicated center treating ketamineassociated uropathy. 9 In this prospective cohort of patients, different tiers of intervention were adopted, ranging from oral medication to more invasive modalities.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Although many recognized that abstinence from ketamine is by far the most effective treatment option, 7 oral or intravesical medication and surgical intervention have been attempted to alleviate the detrimental effect brought along by ketamine abuse on the genitourinary system. 8 We have previously reported a crosssectional study on symptoms and voiding parameters of patients from a dedicated center treating ketamineassociated uropathy. 9 In this prospective cohort of patients, different tiers of intervention were adopted, ranging from oral medication to more invasive modalities.…”
Section: Resultsmentioning
confidence: 99%
“…8,23 Both hydrodistension 24 and augmentation cystoplasty 8 were demonstrated to be effective in selected patients. In our series, we had a stringent criterion to select patients into surgical management, that is, significant symptoms failing noninvasive treatment with more than a 6-month history of abstaining from ketamine abuse.…”
Section: Commentmentioning
confidence: 99%
“…According to Chung et al [2] , all 14 patients who underwent AE for KC had a bladder volume less than 100 mL. The bladder volume of the other 4 patients undergoing AE for KC reported by Ng et al [6] was less than 50 mL. Therefore, the review article published by Jhang et al [7] suggested that patients with KC should undergo AE if their bladder capacity is less than 100 mL with low bladder compliance.…”
Section: Discussionmentioning
confidence: 99%
“…However, the poorest outcome was only 200 mL. In the series published by Ng et al [6], 2 patients had a bladder volume greater than 400 mL. However, the other 2 cases exhibited much smaller bladder volumes.…”
Section: Discussionmentioning
confidence: 99%
“…However, none have shown lasting or significant success, especially if ketamine abuse continues 2. Treatment failure and disease progression often requires more invasive management ranging from hydrodistension to urinary diversion and augmentation cystoclasty 4 5. In contrast, few studies have commented on upper tract involvement.…”
Section: Discussionmentioning
confidence: 99%